Influence of internal fluid velocities and media fill ratio on submerged aerated filter hydrodynamics and process performance for municipal wastewater treatment - Holloway, Timothy G.; Soares, Ana (Elsevier, 2018)
Submerged aerated filters (SAFs) treat wastewater to achieve stringent organic carbon and ammonium (NH4+) effluent consents. Currently SAF design follows a black box approach, where inlet and outlet contaminant concentrations are monitored, with little consideration for internal hydrodynamic conditions. Although tracer tests have been used on bioreactors, integrated monitoring of internal fluid velocities, mixing characteristics and process performance has not been established for SAFs. Tracer tests were performed on a 7.74 m3 SAF, with internal recirculation at 100, 75, 50, 25 and 0% media fill ratios with and without biofilm on the media surface. Results suggested that, SAF internal hydrodynamic conditions directly influenced process performance and media fill ratios could be manipulated to provide optimum conditions for removal of biochemical oxygen demand (BOD5) and NH4+. A 50% media fill ratio showed optimum hydrodynamic conditions for BOD5 removal, with a removal efficiency of 70% (mass removal of 1.59 kg m−3 d−1). A 100% media fill ratio showed optimum hydrodynamic conditions for NH4+ removal, with a removal efficiency of 60% (mass removal of 0.14 kg m−3 d−1). Therefore optimisation of internal hydrodynamic conditions is key for selective contaminant removal and achieving high effluent quality.
Keywords: Biofilter; Biofim bioreactor; Hydrodynamics; Tracer test; SAF; Wastewater